Phagocytic elimination of synapses by microglia during sleep. Issue 1 (19th August 2019) - Choudhury, Mohammed E.; Miyanishi, Kazuya; Takeda, Haruna; Islam, Afsana; Matsuoka, Nayu; Kubo, Madoka; Matsumoto, Shirabe; Kunieda, Takeharu; Nomoto, Masahiro; Yano, Hajime; Tanaka, Junya
Abstract: Synaptic strength reduces during sleep, but the underlying mechanisms of this process are unclear. This study showed reduction of synaptic proteins in rat prefrontal cortex (PFC) at AM7 or Zeitgeber Time (ZT0), when the light phase or sleeping period for rats started. At this time point, microglia were weakly activated, displaying larger and more granular somata with increased CD11b expression compared with those at ZT12, as revealed by flow cytometry. Expression of opsonins, such as complements or MFG‐E8, matrix metalloproteinases, and microglial markers at ZT0 were increased compared with that at ZT12. Microglia at ZT0 phagocytosed synapses, as revealed by immunohistochemical staining. Immunoblotting detected more synapsin I in the isolated microglia at ZT0 than at ZT12. Complement C3‐ or MFG‐E8‐bound synapses were the most abundant at ZT0, some of which were phagocytosed by microglia. Systemic administration of synthetic glucocorticoid dexamethasone reduced microglial size, granularity and CD11b expression at ZT0, resembling microglia at ZT12, and increased synaptic proteins and decreased the sleeping period. Noradrenaline (NA) suppressed glutamate‐induced phagocytosis in primary cultured microglia. Systemic administration of the brain monoamine‐depleting agent reserpine decreased NA content and synapsin I expression in PFC, and increased expression of microglia markers, C3 and MFG‐E8, while increasing the sleeping period. A NA precursor l ‐threo‐dihydroxyphenylserine abolished the reserpine‐induced changes. These results suggest that microglia may eliminate presumably weak synapses during every sleep phase. The circadian changes in concentrations of circulating glucocorticoids and brain NA might be correlated with the circadian changes of microglial phenotypes and synaptic strength. Main Points: Microglia may be responsible for sleep/wake cycle by eliminating synapses that are opsonized with complement C3 and MFG‐E8 around the onset of sleep. Circadian changes of glucocorticoids and noradrenaline levels may affect the activity of microglia.